Martian Atmospheric CO2 and Pressure Profiling With Differential Absorption Lidar: System Consideration and Simulation Results. Issue 11 (27th October 2021) - Lin, B.; Liu, Z.
Abstract: This study explores a new concept of Martian differential absorption Lidar operating at the 2‐μm CO2 absorption band for atmospheric CO2 and pressure observations. For the considered system, two or more closely spaced wavelengths are selected, so that environmental factors such as surface reflection, atmospheric scattering, and absorptions from other trace gases on the lidar return signals are very similar for all selected wavelengths, but the difference in CO2 absorption is substantial. Thus, Martian CO2 amount and air pressure could be retrieved from the measured CO2 differential absorption optical depth at the selected wavelengths. Simulations based on Mars's environmental conditions and technically feasible lidar systems show that lidar returns from the surface could have sufficient signal strengths that allow surface air pressure measurements with 1 Pa precision after a horizontally 5‐km averaging when dust optical depth is smaller than 1.5. Even when the dust optical depth increases to 3, the uncertainty in the air pressure and column CO2 amount measurements with a random error is still smaller than 1%. In the presence of moderate dust aerosol loads and with the optimal selection of offline and online wavelengths, atmospheric CO2 and pressure profiles could also be retrieved from the surface up to an ∼13‐km altitude with the random error smaller than 1% for a horizontal resolution of 100 km and a vertical resolution of 100 m during night or 400 m during day. These CO2 and pressure measurements would significantly improve weather and climate modeling and prediction. Key Points: A differential absorption lidar approach is described that allows precise remote sensing of Martian atmospheric CO2 and pressure from orbit The CO2 and pressure measurements will allow improved modelling of the Martian weather and climate